Hindi Dialects Phonological Transfer Rules for Verb Root Cala - Mishra, Diwakar; Bali, Kalika (Proceedings of O-COCOSDA 2010, 2010)
Most Natural Language Processing (NLP) applications need to account for synchronic variations in a language as represented by its major dialects. However, most corpora available for the training and development of such systems tend to be dialect neutral. A framework that models synchronic variation can make NLP and Speech technology systems more robust to dialect variations. In this paper we present basic phonological transfer rules from standard Hindi to a number of its prominent dialects. We believe that this can be the first step towards a more general model for dialect variation in Hindi. The rules here describe morphophonemic change in simple verb forms between dialects taking the example of verb root cǝlǝ.